Randomised controlled trials performed in sub-saharan Africa : epidemiology, methodology and interventions description - (:unkn) unknown (My University, 2017)
Sub-saharan Africa (SSA) is characterized by a high population growth and a significant poverty. In addition, this area deals with a burden of disease due to both traditional infection diseases and the emerging chronic diseases. Randomised controlled trials (RCTs) taking into account the local context are needed to strength health policy and to improve the population health. However, because of constraint research capacities, RCTs performed in SSA must investigate relevant research questions, biases must be avoided in methods, and health interventions evaluated must be reported completely for easing implementation in current clinical practice. Such efforts help to avoid waste of research. Our objectives were to describe the epidemiology of SSA RCTs, and then to evaluate the methodological quality as well as the reporting of evaluated interventions. On the one hand, our works highlighted that SSA RCTs mainly focused on diseases of the highest burden in that area, although they were frequently funded by high-income countries, and most of the corresponding authors were affiliated to those countries. In the other hand, we have shown that methods at high risk of bias can be avoided through simple methodological adjustments of minor cost. Improving the methodological quality of SSA RCTs implies a large dissemination of available methods at low risk of bias and guidelines on the complete reporting of interventions. Furthermore, understanding barriers and facilitators to the uptake of those methods and guidelines is equally required.
Keywords: African Research